Influence Of Social Skills on Clients’ Motivation to Recover at BNN Baddoka Rehabilitation Center - Nur Ainun Amir; Muh. Daud; Faradillah Firdaus (PT ARRUS Intelektual Indonesia, 2023)
Motivation to recover is the client's drive to achieve recovery. Meanwhile, social skills are the client's ability to interact with other individuals in an effective way. In the process of achieving recovery, individuals need to have social skills in order to get good relationships with other individuals so that they feel owned and valued. This study aims to determine the effect of social skills on the motivation to recover rehabilitation clients. This research uses quantitative methods. This study involved clients at the BNN Baddoka Rehabilitation Center, Makassar City (N = 66). The sampling technique in this study used saturated samples. The measuring instrument used is a scale of recovery motivation and social skills compiled by the researcher. Data analysis used is simple regression through SPSS 22.00. Data analysis obtained a significance value (p) of 0.017 (p < 0.05), so Ha was accepted with an influence of 8.6%. The results of this study indicate that there is a positive relationship between social skills and motivation to recover in clients. This research has implications for the fields of social psychology and health psychology and is useful for the psychological well-being of clients in undergoing a rehabilitation period.